OPTIMALISASI MEDIA PEMBELAJARAN BERBASIS TRADISI LISAN ACEH UNTUK MENINGKATKAN KREATIVITAS, MOTIVASI, DAN KETERAMPILAN BERPIKIR KRITIS SISWA - Teuku Muhammad Husni; Ichsan; Saniman Andri Kafi; Zulfahmi (JURNAL KREASI RAKYAT, 2025)
This study explores the potential of Acehnese oral traditions, including fables, pantuns, and poems, as learning media to enhance students' creativity, motivation, and critical thinking skills. Using a qualitative approach, this study evaluates the effectiveness of these oral traditions in creating interesting, innovative, and meaningful learning experiences. This approach is expected to be an innovative solution to the challenges of contemporary education that often tend to ignore local cultural values ​​in their learning practices. This study uses a qualitative approach. In its implementation, this study combines several data collection methods, namely classroom observation, interviews with teachers, and analysis of teaching materials. The teaching materials used in oral tradition-based learning are also analyzed to identify cultural elements that are integrated into the learning materials. The findings show that the integration of local cultural values ​​through oral traditions not only increases students' enthusiasm for learning, but also develops critical thinking and collaboration skills. These oral traditions present a great opportunity to connect learning with local wisdom, resulting in a more relevant and character-oriented learning process. Recommendations from this study include the need to align oral tradition-based learning methods with modern curricula to achieve optimal learning outcomes, while ensuring the preservation of Acehnese cultural heritage among the younger generation.